A educação geográfica na educação de pessoas jovens e adultas – EJA/Erechim/RS - Moterle, Juciela (2021)
This research entitled "Geographical education in the education of young and adult people - EJA / Erechim / RS", has the general objective of understanding how geographic education can contribute to the reading of the world that YAE subjects build about the spaces of Society, seeking present theoretical studies to deepen the concepts related to geographic education and work in YAE. The specific objectives are to map productions that deal with geographic education and work as an educational principle in Youth and Adult Education; situate the historical context of YAE in Brazil, in the city of Erechim/RS, and in the researched institution; analyze the work concepts that students indicate and how they perceive the work phenomenon in geographic education, and situate the pedagogical devices that geographic education has to contribute to a critical reading of the world of work. The research has a qualitative approach (Minayo, 2010), of exploratory type (Gil, 2008), and its data analysis technique is content analysis (Bardin, 2011), based on empirical data obtained from semi-structured interviews (Gil, 2002) with EJA students from a school in Erechim/RS. The theoretical basis that supported the investigation included authors such as Haddad and Di Pierro (2000), Di Pierro, Joia and Ribeiro (2001), Arroyo (2006, 2013), Laffin (2016), Sanceverino (2017), Thomaz (2002), Alves and Cardoso (2010), Santos (2011), Serra (2019), Kaercher (1996), and others. Four axes were identified that are articulated in the comprehension of the phenomenon studied: how EJA students see geographic education; the understanding they have about work; their perception of the influence of geographic education on the way to understand the dynamism of social reality and the contribution of geographic education to the understanding of the work world. The results indicate that the participants see that geographic education allows them to reflect on the space and the actions that take place in it. The work represents for them the possibility of being active participants in society, not observing, however, the idea of work as a possibility to modify the space and other structures of society. It is also verified that they realize that, with geographic education, they get knowledge about the transformation of societies, but they do not demonstrate that they understand the breadth of geographic education, encompassing the universe of ideas that govern the political, economic, and social models of nations. They note some contribution of geographic education in understanding the world of work, however, they do not point to perceptions and understandings related to the depth of economic, political, social, cultural, and, particularly, environmental transformations. The conclusions of this research demonstrate that, with Geography classes aimed at identifying and analyzing the relationships that take place in the world of work, it is possible to raise the critical awareness of YAE students, so that they are able, at the end of their studies, to express their ideas about the world of work, about the relationships that involve the worker status and, fighting for better conditions. An intervention proposal is presented as a product of the research, aiming to contribute to the qualification of students' education.